Special papersA fatal outcome of thoracic aortic aneurysm in a male patient with bicuspid aortic valve - Milanowska, Blanka; Michalak, Ewa; Michałowska, Ilona; Szpakowski, Eugeniusz; Konopka, Anna; Klisiewicz, Anna; Bilińska, Zofia Teresa (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Thoracic aortic aneurysm is often an asymptomatic but potentially lethal disease if its most catastrophic complication – aortic dissection – occurs. Thoracic aortic dissection is associated with a high mortality rate despite ongoing improvement in its management. We report a fatal outcome of thoracic aortic aneurysm in a male patient with bicuspid aortic valve. The patient was qualified for elective surgery of the ascending aorta and aortic valve at the age of 39 but he did not agree to undergo the proposed procedure. Three years later, he experienced acute aortic dissection and died despite a prompt diagnosis and complex management.